2010
DOI: 10.5424/sjar/2010082-1189
|View full text |Cite
|
Sign up to set email alerts
|

Tillage system does not affect soil macrofauna in southeastern Buenos Aires province, Argentina

Abstract: Soil degradation increased incessantly in the Pampas region of Argentina, due to the intensification of agricultural activities, when carried out with conventional tillage (CT) systems. No-tillage system was adopted as conservation practices by the farmers. The objectives of this study were: a) to determine the macrofauna taxa and their relative abundance under CT and NT in two different seasons; and b) to evaluate soil tillage and seasonal effects on the density of the main macrofauna taxa. The study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
(25 reference statements)
3
18
3
1
Order By: Relevance
“…These numbers are comparable to what Dezi et al (2013) found in agricultural soils in India (16.000 ind.m 2 ) and are higher than found by Chan andHeenan (1995) (2000 ind.m 2 ) in arable lands in Australia. Further studies included data on enchytraeid abundance determined by handsorting of soil monoliths in Brazil, such as Brown et al (2001) Manetti et al (2010), appr. 750 ind.m 2 in no-tillage cropping system.…”
Section: Abundance Of Enchytraeids In (Sub)tropical Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers are comparable to what Dezi et al (2013) found in agricultural soils in India (16.000 ind.m 2 ) and are higher than found by Chan andHeenan (1995) (2000 ind.m 2 ) in arable lands in Australia. Further studies included data on enchytraeid abundance determined by handsorting of soil monoliths in Brazil, such as Brown et al (2001) Manetti et al (2010), appr. 750 ind.m 2 in no-tillage cropping system.…”
Section: Abundance Of Enchytraeids In (Sub)tropical Soilsmentioning
confidence: 99%
“…However, studies on their ecology using standardized methods and thus, globally comparable results, are restricted to a couple of publications (Römbke and Meller, 1999;Römbke et al, 2007) which used the cold wet extraction. In South America, there are a few other reports on abundance of enchytraeids, which numbers were determined by handsorting, but taxonomic groups were not assessed (Sturm, 1978;Vaçulik et al, 2004;López et al, 2005;Aquino et al, 2008;Manetti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The present study is a continuation of research (Manetti et al, 2010) conducted to evaluate the influence of CT and NT on soil fauna in two traditional crops, wheat and maize, in Balcarce, Buenos Aires, Argentina. The climate in this area is mesothermal, humid to subhumid (according to the Thornthwaite classification) or temperate humid without a dry season (according to the Köppen classification).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were taken in the same agricultural fields under production used by Manetti et al (2010). These fields were located within 30 km of the Balcarce Agricultural Experimental Station of the National Institute of Agricultural Technology (37°45′45″ S, 58°18′3″ W).…”
Section: Methodsmentioning
confidence: 99%
“…10 ). Manetti et al ( 2010 ) in Argentina also found that tillage had little effect on soil macrofauma and attributed this to the fact that tillage had little effect Note that the impact of no-till on earthworm density and microbial biomass depends on the use of organic amendment. Moreover, microbial activity is particularly affected by the application of herbicides (Adapted from Mijangos et al 2006 ) on the soil content in organic matter.…”
Section: Tillagementioning
confidence: 99%